The Ethics of Power. - da Costa, Marta Nunes (International Journal of the Humanities, 2005)
Having Foucault's triptical project of defining technologies of knowledge, power and of the self as framework, I will provide an articulation of the modes of existence of the (transmuted) modern subject and I will argue why is it relevant to redefine individuality today. In a society where power is indissociable of knowledge and where ideals are easily converted into ideologies (of consumerism in its link with liberty and democracy) one must inquiry into the actual and possible space for an ethical and political life. The first step consists in establishing the analytical distinction between subjectivity, individualism and individuality. For this I will articulate Foucault's conception of authorship (as transmutation of the subject in discursive practices), subject (as locus of power within the institutional context) and self (as promise of freedom within the personal ethical sphere). Confronted with the limitations of the Foucauldian project (specially the strict, personal and local effects of his ethics), I will re-take Kantian heritage in its concern with freedom and human emancipation, as well as Adorno's model of ‘culture industry’. Based on the articulation of the three authors, I will accomplish the second goal of my paper, namely, of providing an alternative a positive model of individual autonomy today.